O discurso eleitoral da Folha de S.Paulo e O Estado de S.Paulo na campanha eleitoral de 2010 - Orlandini, Romulo Augusto (2012)
The objective of this thesis was to discuss the election of 2010 under the bias of print journalism. The analysis was made by the editorial in the Folha de S.Paulo and O Estado de S.Paulo. We had as hypothesis that newspapers represent concepts and ideas of the reading public medium that would influence the editorial published in the coverage of the three major presidential candidates. Then, we compare the final result of the election with the different approaches of the editorials in relation to candidates in order to know whether an editorial could influence the election or not. The theory was founded on the philosophy of language, concept and method created by Mikhail Bakhtin and based on ideological correctness of the text and context, relating the socio-historical moment. The theory was founded on the philosophy of language, concept and method created by Mikhail Bakhtin and based on the correlation of the text and ideological context, relating the socio-historical moment. The qualitative results showed that O Estado de S.Paulo quoted 14.02% of 442 collected texts cited presidential candidates, while the Folha de S.Paulo quoted presidential candidates in 22.8% of 285 texts - with the name appearing Rousseff on average 59 times, Jose Serra quoted 37.5 and Marina Silva quote 10.5. The qualitative result proved the trajectory of incandescent Election: Nine themes were prevalent in newspaper articles and revealed a complex scenario of the race to the presidency. We observed that the effect of former President Luiz Inacio Lula da Silva and political scandals have earned high relief - generating protests from editorial writers - highlighting the role of the press watchdog - to the point of the O Estado de S.Paulo first take position in an election. In the other one was related issues directly with the electoral rules, the relationship with government plans while the other (FARC, Abortion/religion and Privatization) resumed discourses that traditionally appear at critical moments in which it is called when it is necessary to trigger the review public